Insurgency, political stability and economic performance in post-Saddam Iraq: an evaluation - Jalal Nore, Abdul Wahed Jalal Nore; Abdul Ghani, Ahmad Bashawir (Canadian Centre of Science and Education, 2009)
On March 20, 2003, the coalition forces headed by the United States of America launched Operation Iraqi Freedom to remove the regime of Saddam Hussein. By mid-April, major fighting was essentially over, and on May 1, the United States declared an end to major combat operations. With that declaration, the coalition forces faced with a very serious challenge to ensure stability in the post-conflict period and a peaceful political transition to a new and democratic Iraqi government. However, despite the continuing power of insurgency and the sectarian violence, Iraq is gradually gearing into a kind of constitutional process and political development. The election of January 2005, the negotiation of the constitution in the summer of that year, the referendum of October 15, which ratified the constitution and the second general election in mid December, all is a sign of functioning of political and constitutional development. The new constitution was written with the hope that for the diverse groups in Iraq to run their mutual relations in such a way that the dialogue between fighting parties shifts from a battle field into a political settlement. However, such political settlement, in spite of the huge presence of US forces, has been extremely slow. Domestic political elites have shown very little